Strategies To Improve Member Satisfaction Through Analysis Of The Work Environment, Motivation, And Service Quality At CU Tunas Harapan Kota Batam: - Nuraeni, Brigida Endah; Sumarya, Edi (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2025)
This study aims to formulate strategies to improve member satisfaction by analyzing the influence of work environment, motivation, and service quality at the CU Tunas Harapan Savings and Loan Cooperative in Batam City. A quantitative approach was employed, involving a population of 190 individuals, with a purposive sampling technique used to select 129 respondents. Data were collected through an online questionnaire distributed via Google Form and analyzed using SPSS version 26. The results show that, partially, the work environment has a positive and significant effect on member satisfaction (t-value = 2.115; p-value = 0.036). However, motivation and service quality did not have a significant individual impact (t-value = 0.981 and 1.159; p-value = 0.328 and 0.249, respectively). Simultaneously, all three independent variables work environment, motivation, and service quality have a positive and significant effect on member satisfaction (F-value = 19.194; p-value = 0.000). These findings suggest that strategies to improve member satisfaction at CU Tunas Harapan should prioritize strengthening the work environment, while also considering improvements in motivation and service quality as integral components of comprehensive and sustainable cooperative development. Keywords:Member satisfaction, work environment, motivation, service quality, savings and loan cooperative.